Equívocos, mentiras, ocultaciones y medias verdades en la historia de la cartografía impresa valenciana (1584-1797) - Alfredo Faus Prieto (Cuadernos de Geografía de la Universitat de València)
The history of cartography is replete with errors of difficult correction. Maps with dating and authorship bearing apocryphal luggage, the copies that remain ritually original content, the well or malicious-intentioned occultation data, references to delineations that no one has seen or onomastic confusion are common examples in this regard. In the case of valencian printed cartography, these misunderstandings affect maps and authors of great prestige and have led to a history fraught with common places that do not conform to reality. This article seeks to correct some of them from the critical review of the latest research in this field.